Public Perception of the Effectiveness of Public Administration Reforms in Bangladesh - Ariful Islam Siddique; Md Mainuddin (MultiTech Publisher, 2023)
The Sustainable Development Goals (SDGs) represent a comprehensive blueprint for global endeavors to address socio-economic and environmental challenges by 2030. This study delves into the intricate tapestry of SDG implementation within the public administrative realm of Bangladesh. By amalgamating quantitative data, qualitative insights, and comprehensive analyses, the research uncovers the commendable progress made, the innovative strategies employed, and the multifaceted challenges encountered. From the integration of SDGs into national agendas to the pioneering SDG tracker, Bangladesh's commitment is evident. However, bureaucratic constraints, resource limitations, and practical applicability of initiatives emerge as areas requiring nuanced interventions. As Bangladesh charts its path towards 2030, this research underscores the importance of continuous adaptation, collaboration, and a unified vision. This study not only elucidates Bangladesh's SDG journey but also contributes to the global narrative of sustainable development aspirations.